In situ observations on the dentition and oral cavity of the Neanderthal skeleton from Altamura (Italy) - Riga, Alessandro (PLoS One, 2020)
The Neanderthal specimen from Lamalunga Cave, near Altamura (Apulia, Italy), was discovered during a speleological survey in 1993. The specimen is one of the most complete fossil hominins in Europe and its state of preservation is exceptional, although it is stuck in calcareous concretions and the bones are mostly covered by calcite depositions. Nevertheless, it is possible to carry out some observations on craniodental features that have not previously been described. In this work, we present an account of the oral cavity, made possible by the use of a videoscope, which allowed us to reach some hidden parts of the mandible and palate. This is the first detailed overview of the teeth and maxillary bones of the Neanderthal skeleton from Altamura. The dentition is almost complete. However, two teeth (upper right P3 and upper left M1) were lost ante mortem and four teeth (lower right I1 and P3 and lower left I1 and I2) were lost most probably post mortem. Dental wear is marked. The erupted M3s and the inversion of the compensating curve of Wilson in the M1s and M2s but not in the M3s suggest that the individual is fully adult, but not old. Although most of the teeth have their roots exposed for several millimeters, the periodontal bone appears to be in good condition overall, except in correspondence of the two ante-mortem tooth losses. X-rays of the anterior teeth show a periapical lesion, probably linked to the advanced dental wear. We also observed a weak expression of taurodontism in the posterior dentition and the presence of a retromolar space, features consistent with an attribution to the Neanderthal hypodigm; this attribution is also supported by aspects of the cranial morphology, the morphometric analysis of the scapula and preliminary mtDNA data. There is also a well-developed palatine torus, to the best of our knowledge a feature not previously described in Neanderthals.